ПРОЕКТИРОВАНИЕ И ВНЕДРЕНИЕ СИСТЕМЫ МОНИТОРИНГА ОБУЧЕНИЯ - Каипова, С.К. (SCIENCE and SOCIETY, 2023)
The article discusses and presents the design and implementation of monitoring in the education system.